Capturing social network effects in technology adoption: The spatial diffusion of hybrid rice in Bangladesh - Ward, Patrick S.; Pede, Valerien O. (Wiley, 2015)
In this paper, we demonstrate a method for measuring the effect of spatial interactions on the use of hybrid rice using a unique, nationally representative data set from Bangladesh. In order to circumvent the ‘reflection problem’, we consider an identification and estimation strategy employing a generalised spatial two‐stage least squares procedure with near‐ideal instruments to effectively identify causal influences. Results indicate that neighbour effects are a significant determinant of hybrid rice use. Further, using two specifications of spatial network systems, one based on same‐village membership (irrespective of distance) and the other based on geographical distance (irrespective of village boundary), we demonstrate that a network including nearby hybrid rice adopters is more influential than a network of more distant hybrid rice adopters, and merely having a network with a large number of adopters may be relatively meaningless if they are far away. Furthermore, we show that these network effects are much more important to hybrid cultivation than interactions with agricultural extension officers.